The evolving role of radiation in pancreatic cancer - Malla, Midhun; Fekrmandi, Fatemeh; Malik, Nadia; Hatoum, Hassan; George, Sagila; Goldberg, Richard M.; Mukherjee, Sarbajit (Frontiers in Oncology, 2023)
Pancreatic cancer is the fourth leading cause of cancer mortality in the United States. Chemotherapy in resectable pancreatic cancer has improved survival by 10-20%. It only converted 10-30% of the borderline resectable and locally advanced pancreatic cancers to be surgically resectable. Radiation therapy has a documented role in managing localized pancreatic cancer, more so for borderline and locally advanced pancreatic cancer, where it can potentially improve the resectability rate of a given neoadjuvant treatment. The role of radiation therapy in resected pancreatic cancer is controversial, but it is used routinely to treat positive margins after pancreatic cancer surgery. Radiation therapy paradigms continue to evolve with advancements in treatment modalities, delivery techniques, and combination approaches. Despite the advances, there continues to be a controversy on the role of radiation therapy in managing this disease. In this review article, we discuss the recent updates, delivery techniques, and motion management in radiation therapy and dissect the applicability of this therapy in pancreatic cancer.